Erasmus programme effects: a Spanish case - Urquía-Grande, Elena; del Campo, Cristina (Papeles de Europa, 2016)
The internationalisation of Higher Education (HE), as part of the European integration programs, has become a priority not only for governments but also for universities. The Faculty of Economics and Business (Complutense University of Madrid) has promoted the European mobility as part of the internationalisation strategy through the Erasmus programs for students’ mobility since its beginning. However continuous endeavour must be made. The objective of the present research is to study the internationalisation of HE. For this purpose a survey was designed to measure the degree of outgoing Erasmus students’ satisfaction. Multivariate statistic techniques were run to observe that variables such as academic and cultural experiences in the host Universities determine the students´ overall satisfaction. Multiple maps of relationships within variables were found demonstrating that students perceive as most important they develop academic and socio-cultural competences together with linguistic skills when studying abroad.